2011
DOI: 10.1039/c1jm10722d
|View full text |Cite
|
Sign up to set email alerts
|

Organic–inorganic nanocomposite bilayers with triple shape memory effect

Abstract: Various amounts of silica nanoparticles were chemically incorporated into amorphous polyurethanes (PU) of two different molecular weights by sol-gel reactions, and the effects were studied in terms of mechanical, dynamic mechanical, dual, and triple shape memory effects (DSME and TSME) of the nanocomposite films. It was found that the silica particles act as multifunctional cross-links as well as reinforcing fillers and significantly augmented the glassy and rubbery state moduli, yield strength, break strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 25 publications
1
67
1
Order By: Relevance
“…Recently, polyether based polyurethane/silica nanocomposites were prepared by using solegel process. These crosslinked hybrid nanocomposites were obtained by adding fumed silica directly [32] or dispersed in a solvent [33] into organoalkoxysilane end-capped prepolymer solutions. On the other hand, there is no report in the literature dealing with the use of silica sol "as synthesized and aged" in basic media for the preparation of polyether-based TPU/silica nanocomposites, specifically through solution blending of the copolymer and the silica sol.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polyether based polyurethane/silica nanocomposites were prepared by using solegel process. These crosslinked hybrid nanocomposites were obtained by adding fumed silica directly [32] or dispersed in a solvent [33] into organoalkoxysilane end-capped prepolymer solutions. On the other hand, there is no report in the literature dealing with the use of silica sol "as synthesized and aged" in basic media for the preparation of polyether-based TPU/silica nanocomposites, specifically through solution blending of the copolymer and the silica sol.…”
Section: Introductionmentioning
confidence: 99%
“…Following these concepts, the triple-SME has been realized in a number of polymer systems [54,[110][111][112][113][114][115][116][117]. Although in theory, we can achieve an infinite number of intermediate shapes [109,118], the significance of the SME in each intermediate shape is reduced with the increase of the number of the intermediate shapes.…”
Section: Multiple-sme (Shape Memory Effect)mentioning
confidence: 99%
“…18,19 The llers modied by chemical hybridization can achieve multifunctional crosslinking with polymers, thereby enhancing the rubber elasticity and strain recovery. 20 Among the various chemical hybridization agents, silane coupling agents with general formula of R-(CH 2 ) n -Si-(OR 0 ) 3 are widely used to modify llers or polymers. 21 Several literature works have reported that the silane coupling agents generate bridging with the surface of llers, and greatly enhance the physical bonding between the llers and the polymer matrix.…”
Section: 10mentioning
confidence: 99%